Morphology and karyology of Thinopyrum elongatum (Host) D.R. Dewey (Botanica Orientalis: Journal of Plant Science, 2019)
Thinopyrum elongatum (Host) D.R. Dewey, one of the perennial species of Triticeae, is very important grass for the improvement of wheat owing to the presence of several useful genes in its genome. Present study attempted to characterize Thinopyrum elongatum (strain ID: TACBOW0120) collected by Dvorak and maintained in Kyoto University, Japan. The external morphology of plant was carried out taxonomically. Microscopic examination was done for pollen grain and mitotic chromosomes of root cells. Altogether, 14 chromosomes were observed and classified into five pair of more or less metacentric chromosomes and two pairs of sub-metacentric chromosomes with satellites (formula 2n=2x=10m+4SATsm=14). Pollen grains were spherical and measured about 38 micrometers. The morphological traits characterized will be useful to study wheat – T. elongatum disomic addition lines in which each pair of chromosomes of T. elongatum are maintained in 7 different types of common wheat cultivar “Chinese Spring”.